From Paper Files to Web-Based Application for Data-Driven Monitoring of HIV Programs: Nigeria's Journey to a National Data Repository for Decision-Making and Patient Care - Dalhatu, Ibrahim; Aniekwe, Chinedu; Bashorun, Adebobola; Abdulkadir, Alhassan; Dirlikov, Emilio; Ohakanu, Stephen; Adedokun, Oluwasanmi; Oladipo, Ademola; Jahun, Ibrahim; Murie, Lisa; Yoon, Steven; Abdu-Aguye, Mubarak G.; Sylvanus, Ahmed; Indyer, Samuel; Abbas, Isah; Bello, Mustapha; Nalda, Nannim; Alagi, Matthias; Odafe, Solomon; Adebajo, Sylvia; Ogorry, Otse; Akpu, Murphy; Okoye, Ifeanyi; Kakanfo, Kunle; Onovo, Amobi Andrew; Ashefor, Gregory; Nzelu, Charles; Ikpeazu, Akudo; Aliyu, Gambo; Ellerbrock, Tedd; Boyd, Mary; Stafford, Kristen A.; Swaminathan, Mahesh (Methods of Information in Medicine, 2023)
Background Timely and reliable data are crucial for clinical, epidemiologic, and program management decision making. Electronic health information systems provide platforms for managing large longitudinal patient records. Nigeria implemented the National Data Repository (NDR) to create a central data warehouse of all people living with human immunodeficiency virus (PLHIV) while providing useful functionalities to aid decision making at different levels of program implementation.Objective We describe the Nigeria NDR and its development process, including its use for surveillance, research, and national HIV program monitoring toward achieving HIV epidemic control.Methods Stakeholder engagement meetings were held in 2013 to gather information on data elements and vocabulary standards for reporting patient-level information, technical infrastructure, human capacity requirements, and information flow. Findings from these meetings guided the development of the NDR. An implementation guide provided common terminologies and data reporting structures for data exchange between the NDR and the electronic medical record (EMR) systems. Data from the EMR were encoded in extensible markup language and sent to the NDR over secure hypertext transfer protocol after going through a series of validation processes.Results By June 30, 2021, the NDR had up-to-date records of 1,477,064 (94.4%) patients receiving HIV treatment across 1,985 health facilities, of which 1,266,512 (85.7%) patient records had fingerprint template data to support unique patient identification and record linkage to prevent registration of the same patient under different identities. Data from the NDR was used to support HIV program monitoring, case-based surveillance and production of products like the monthly lists of patients who have treatment interruptions and dashboards for monitoring HIV test and start.Conclusion The NDR enabled the availability of reliable and timely data for surveillance, research, and HIV program monitoring to guide program improvements to accelerate progress toward epidemic control.
Keywords: data warehouse; electronic health records; global health; health information exchange; shared health records